2006
DOI: 10.1002/marc.200600038
|View full text |Cite
|
Sign up to set email alerts
|

Novel Water‐Soluble Poly(m‐benzamide)s: Precision Synthesis and Thermosensitivity in Aqueous Solution

Abstract: Summary: Chain‐growth polycondensations of 3‐aminobenzoic acid methyl esters 1a and 1b, bearing a tri‐ or tetra(ethylene glycol) methyl ether unit on the amino group, respectively, were carried out with lithium hexamethyldisilazide (LiHMDS) as a base and phenyl 4‐methylbenzoate (2) as an initiator in THF at 0 °C. The poly(m‐benzamide)s obtained in the presence of N,N,N′,N′‐tetramethylethylenediamine (TMEDA) possessed narrow molecular weight distributions ($\overline M _{\rm w} /\overline M _{\rm n}$ < 1.2) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Furthermore, poly1 was soluble in not only organic solvents, but also water, although it was less soluble in water than poly(N-TEG-m-benzamide). These solubility characteristics are similar to those of poly(N-TEG-m-benzamide) [21]. The aqueous solution of poly1 exhibited a cloud point when heated in a similar manner to poly(N-TEG-m-benzamide).…”
Section: Solubility and Aqueous Solution Behavior Of Poly1supporting
confidence: 60%
See 4 more Smart Citations
“…Furthermore, poly1 was soluble in not only organic solvents, but also water, although it was less soluble in water than poly(N-TEG-m-benzamide). These solubility characteristics are similar to those of poly(N-TEG-m-benzamide) [21]. The aqueous solution of poly1 exhibited a cloud point when heated in a similar manner to poly(N-TEG-m-benzamide).…”
Section: Solubility and Aqueous Solution Behavior Of Poly1supporting
confidence: 60%
“…This result indicated that the thermotransition of poly1 in an aqueous solution becomes sharper with increasing molecular weight until the molecular weight exceeds a certain value. The cloud point of poly1 was 21-23 °C, which was about 30 °C lower than that of a 0.5 wt.−% aqueous solution of poly(N-TEG-m-benzamide) [21]. One might think that the cloud point of hyperbranched polymer would be higher than that of the corresponding linear polymer because the former is generally more soluble than the latter.…”
Section: Solubility and Aqueous Solution Behavior Of Poly1mentioning
confidence: 85%
See 3 more Smart Citations